2009
DOI: 10.1080/01690960802586188
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural variation of speech-accompanying gesture: A review

Abstract: A note on versions:The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. Please see the 'permanent WRAP url' above for details on accessing the published version and note that access may require a subscription. This article reviews the literature on cross-cultural variation of gestures. Four factors governing the variation were identified. The first factor is the culture-specific convention for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
145
0
12

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(167 citation statements)
references
References 64 publications
(54 reference statements)
5
145
0
12
Order By: Relevance
“…Only the difference between Turkish speech and speech including cospeech gesture codings was significant. These findings are in line with previous research on co-speech gestures (Kita and Özyürek 2003;Kita 2009) which suggests that speakers do gesture when they describe spatial relations. The present study also adds that co-speech gestures can add information (Kendon 2000) which speech lacks, such as in the case of Turkish.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Only the difference between Turkish speech and speech including cospeech gesture codings was significant. These findings are in line with previous research on co-speech gestures (Kita and Özyürek 2003;Kita 2009) which suggests that speakers do gesture when they describe spatial relations. The present study also adds that co-speech gestures can add information (Kendon 2000) which speech lacks, such as in the case of Turkish.…”
Section: Discussionsupporting
confidence: 82%
“…When languages represent space, they map spatial features, Space in sign, speech, and co-speech gestures 443 not one-to-one, but many-to-many onto the linguistic representations (Jackendoff 1996; Slack and van der Zee 2003). However, they differ from each other in many domains of the linguistic representations of space such as morphosyntax (Grinevald 2006), preferences for a reference frame over another in a given situation (Pederson et al 1998;Levinson and Wilkins 2006), conversion of motion event parts to linguistic event segments (Bohnemeyer et al 2007), and gestural productions accompanying spoken language descriptions of space (Levinson 2003;Kita and Özyürek 2003;Kita 2009). These differences are, arguably, reflected in nonlinguistic domains of cognition (see Levinson et al 2002;Majid et al 2004;Haun et al 2011; see also for contrary findings Li and Gleitman 2002;Li et al in press) The studies presented above focused on one of the available modalities in human communication, the audio-vocal modality.…”
Section: Introductionmentioning
confidence: 99%
“…Goldin-Meadow (2004, p. 315) states that unlike language, which is based on codified words and a specific grammar, "gestures convey meaning globally, relying on visual and mimetic imagery." Simultaneously, research has shown variations in how people from different ethnic cultures use gestures (Ekman & Friesen, 1972;Kita, 2009). To exemplify, Matsumoto and Hwang's (2013) comparative study displayed several differences in how people from Sub-Saharan Africa, East Asia, Latin America, Middle East, South Asia, and the United States use emblems (gestures that can occur independent from speech).…”
Section: Identifying Gesturesmentioning
confidence: 99%
“…Gestures also mirror information structure and align with newsworthy or focused information. This coordination means that gestures reflect language-specific meaning in different gestural forms and gestural timing relative to speech (Brown & Gullberg, 2008;Duncan, 2005;Gullberg, Hendriks, & Hickmann, 2008;Kita, 2009;Kita & Özyürek, 2003;McNeill, 1992; (Gullberg, submitted-a). For instance, native French speakers' gestures tend to express the path element of the movement in a simple pointing hand or a gesture with a flat hand shape moving in a given direction.…”
Section: Placement Verbs Across Languages and Modalitiesmentioning
confidence: 99%